Pengembangan Media Video Animasi Menggunakan Aplikasi Canva pada Pembelajaran IPAS di Kelas V Sekolah Dasar - Guslyanto, Runi; Sartono, Sartono (Indo-MathEdu Intellectuals Journal, 2025)
Learning resources that are less varied cause students to become bored, less active, and have difficulty understanding the material presented by the teacher during the learning process. This study aims to develop animated videos using the Canva application in the Science subject in grade V of elementary school that are valid, practical and effective. The type of research used in this study is a mixed-method approach design with the ADDIE development model. The validity test showed that the animated video was valid with a score of 88.57% (material), 96.5% (media), and 96.5% (language). The practicality test from the teacher's response showed that the animated video was practical with a score of 94.28% (SDN 125/1 Awin), 97.14% (SDN 42 Lubuk Ruso), and 94.28% (SDN 125/1 Awin), while the results of the practicality test from the student's response showed the following percentages: 91.78% (SDN 125/1 Awin Class Vb), 94.25% (SDN 125/1 Awin Class Va), and 91.19% (SDN 42 Lubuk Ruso). The results of the effectiveness test from the three schools experienced an increase in the average pre-test and post-test. This shows that the animated video media that has been developed is very suitable for use in the learning process. Thus, the animated video is valid, practical, and effective for use in Pancasila education learning for fourth grade elementary school